A Two-Way Manova Analysis of Study Program and SchoolType on GPA and Study Duration - Epha Diana Supandi (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2026)
This study aimed to examine the effects of Study Program and Type of School as independent variables on students’ academic achievement, measured by Grade Point Average (GPA) and Study Duration as dependent variables, at the Faculty of Science and Technology, UIN Sunan Kalijaga Yogyakarta. The study employed secondary academic data obtained from the faculty’s Academic Office. The sample consisted of 210 undergraduate alumni from six study programs who graduated in May and August 2025. The data were analyzed using Two-Way Multivariate Analysis of Variance (Two-Way MANOVA), followed by Two-Way ANOVA, and post hoc tests using Tukey’s Honest Significant Difference (HSD) and Estimated Marginal Means (EMMs). The results showed that Study Program had a significant effect on both GPA and Study Duration, while Type of School significantly influenced Study Duration but did not significantly affect GPA. In addition, the interaction between Study Program and Type of School significantly affected Study Duration. Post hoc analyses revealed that students from Informatics, Chemistry, and Industrial Engineering achieved significantly higher GPA than Physics students, whereas Biology students tended to have significantly longer study durations compared with several other study programs. Students from MA backgrounds also tended to require longer study duration than students from SMA backgrounds. These findings indicate that academic achievement in higher education is influenced more strongly by disciplinary characteristics than by prior school background alone. The study highlights the importance of curriculum evaluation, academic mentoring, and adaptive learning support systems to improve students’ academic performance and timely graduation.